On costless-renegotiation proofing in binary agency models - Christian Lukas (Managerial and Decision Economics, 2023)
This paper analyzes the occurrence of renegotiation costs in dynamic, binary agency models with a risk-averse agent. I investigate technological interdependence arising from complementary tasks or substitutable tasks across periods. In addition, I analyze stochastic interdependence between periods. The analysis leads to two results. First, the timeliness of performance measures leads to zero costs from renegotiation. Surprisingly, timeliness may arise even in the case of stochastic interdependence. Second, neither technological nor stochastic interdependence is sufficient for renegotiation losses. The former finding is in line with results obtained in the LEN model, but the latter contrasts. In the binary agency model, renegotiation does not harm efficiency as long as raising incentives in the second period is ineffective for inducing higher effort in the first period.
Keywords: 650